Comparative Analysis of Co-Tidal Patterns in the Sunda Strait Using Tide Gauges, Altimetry Data, and TPXO9v4a Global Tide Model - Zulfikar Adlan Nadzir; Agung Pandi Nugroho; Raihan Dema Nurrizal (Universitas Gadjah Mada, 2026)
The Sunda Strait, a narrow and topographically complex passage between Java and Sumatra, presents unique challenges for accurate tidal modeling. This study evaluates tidal dynamics across the strait using three data sources: in-situ tide gauge measurements, Jason-2/3 satellite altimetry (processed with ALES retracking), and the TPXO9v4a global barotropic tidal model. Harmonic analysis was conducted for eight principal constituents across four tide gauge stations, with amplitude and phase comparisons revealing substantial overestimation and lead bias in TPXO—particularly for M2, where amplitude discrepancies exceeded 500%. Altimetry data showed closer agreement, especially in semidiurnal constituents, but remained limited by land contamination and coarse temporal resolution. Co-amplitude and co-phase maps constructed from the datasets revealed complex propagation features, including strong spatial phase gradients and potential amphidromic behavior, not captured by TPXO. Statistical tests confirmed significant differences between model and observational datasets. Additionally, tidal regime analysis using form factor classification confirmed a consistent mixed, mainly semidiurnal regime, though altimetry occasionally overestimated diurnal influence. These findings demonstrate the inadequacy of global tidal models alone in resolving nearshore dynamics and support the use of integrated observational-modeling frameworks for improved regional tidal characterization in Indonesia's coastal waters.